Organisational stressors, coping, and outcomes in competitive sport. Issue 7 (3rd April 2017) - Arnold, Rachel; Fletcher, David; Daniels, Kevin
ABSTRACT: Organisational stressors are associated with positive and negative outcomes in extant literature; however, little is known about which demands predict which outcomes. Extant theory and literature also suggests that coping style may influence an individual's resilience or vulnerability to stressors and, subsequently, their psychological responses and outcomes. The purpose of this study was, therefore, to examine the main effects of organisational stressors and coping styles on various outcomes (e.g., positive and negative affect, performance satisfaction). Sport performers ( n  = 414) completed measures of organisational stressors, coping styles, positive and negative affect, and performance satisfaction. Multiple regression analyses revealed positive relationships of both goals and development stressors (duration and intensity) and team and culture stressors (frequency and intensity) on negative affect. Furthermore, problem-focused coping was positively related to positive affect, and emotion-focused coping was positively related to negative affect. This study furthers theoretical knowledge regarding the associations that both organisational stressors (and their dimensions) and coping styles can have with various outcomes, and practical understanding regarding the optimal design of stress management interventions.